The effect of early castration on weight gain in male rabbits - Qing Z.B.; Xian Z.G.; Hua Z.Y. (Rabbit production in hot climates, 1994)
The study was conducted to test the effectiveness of early castration on weight gain of male rabbits. Twenty male rabbits (initial body weight 0.942-1.283 kg) were used in this experiment. They came from ten litters (two per litter) and were assigned into two groups: one was control group, and the other was test group. These two groups formed a comparison group. The rabbits of the test group were early castrated. Other treatments of the two groups were the same. T-test showed that castration resulted in increasing of average body weight and improving of food efficiency.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)